Advances and challenges in electric unicycle stability: a review of structural design and control mechanisms - Ramli, Noorhidayah; Azizi, Muhammad Azim; Abdul Aziz, Nuraini; Azman, Muhamad Amin (Springer Nature, 2025)
Unicycles possess inherent instability, requiring cohesive design and control mechanisms to maintain balance. This review examines various control strategies and structural designs that enhance unicycle stability. The position of the center of gravity plays a critical role, and it is influenced by factors such as chassis design, supporting structures, and battery placement. Control systems process data from sensors and make adjustments using methods that range from simple methods ranging from simple proportional-integral-derivative (PID) controllers to advanced approaches such as fuzzy logic and predictive control. Sensors, including accelerometers and gyroscopes, detect inclination and movement that maintain an upright position. The ability to perform real-time adjustments can be enhanced by components such as motors and reaction wheels. Additionally, hardware such as Arduino and SoPCs enhances stability control by providing real-time computing capabilities. This review highlights gaps in current knowledge by gathering insights from scholarly articles, research papers, and patents. This research contributes ideas and knowledge toward improving electric unicycles in terms of stability, efficiency, and suitability for real-world applications.